2020
DOI: 10.4491/eer.2020.524
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of flumequine by N-doped TiO2 catalysts under simulated sunlight

Abstract: Flumequine (FLU) is one of the most used fluoroquinolone antibiotics in intensive aquaculture, however, it has become a typical pollutant in water environment at present due to inappropriate use. Therefore, it is necessary to develop facile techniques for efficient degradation of FLU. In this work, three N-doped TiO2 photocatalysts were synthesized for degradation of FLU. The obtained photocatalysts were characterized using scanning electron microscopy (SEM), X-ray diffraction (XRD), X-ray photoelectron spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“… 12 Zeng et al indicated that the TiO 2 /AN sample exhibited high photocatalytic performance under simulated sunlight irradiation, and 100% removal efficiency of FLU was achieved after 4 hours of illumination. 13 Ashrafi et al found that the effective removal of FLU from aqueous solution by laccase from Trametes versicolor , and the removal rate can reach 77.76% under the optimum conditions. 14 Many studies have reported that hydroxyl radical (HO˙, E 0 = 2.5–3.1 V, <1 μs) driven advanced oxidation processes (AOPs) such as photocatalytic and Fenton processes could degrade FLU effectively.…”
Section: Introductionmentioning
confidence: 99%
“… 12 Zeng et al indicated that the TiO 2 /AN sample exhibited high photocatalytic performance under simulated sunlight irradiation, and 100% removal efficiency of FLU was achieved after 4 hours of illumination. 13 Ashrafi et al found that the effective removal of FLU from aqueous solution by laccase from Trametes versicolor , and the removal rate can reach 77.76% under the optimum conditions. 14 Many studies have reported that hydroxyl radical (HO˙, E 0 = 2.5–3.1 V, <1 μs) driven advanced oxidation processes (AOPs) such as photocatalytic and Fenton processes could degrade FLU effectively.…”
Section: Introductionmentioning
confidence: 99%
“…An Acquity UPLC BEH C18 column (1.7 μm, 2.1 × 50 mm) was used to accomplish the separation. More detailed experimental parameters were described in our recent research report (Zeng et al, 2021).…”
Section: Degradation Intermediates Identificationmentioning
confidence: 99%
“…However, despite all these benefits, as TiO 2 has a wide band gap (3.2 eV), its photocatalytic efficiency is less in removing pollutants under different light sources. Therefore, to enhance the photocatalytic activity of TiO 2 , researchers employed different processes like metal doping such as Ag, Mn, Cu, V, Mo, Cr, Fe, and Zn and non-metal doping such as P, C, N, S, and TiO 2 nanocomposites . Numerous studies have found that doping metal oxides with transition metals can improve the photocatalytic activity, owing to a shift in the absorption region from UV to visible light due to a change in their electronic structure .…”
Section: Introductionmentioning
confidence: 99%